FAKTOR-FAKTOR YANG MEMPENGARUHI KESEDIAAN KARYAWAN MEMBAYAR ZAKAT PROFESI MELALUI PEMOTONGAN GAJI ( STUDI KASUS DIREKTORAT JENDERAL PERBENDAHARAAN NEGARA DEPARTEMEN KEUANGAN REPUBLIK INDONESIA) - Anindita Dianingtyas (Media Ekonomi, 2011)
This study aims to look at what factors affect the willingness of employees to pay profession zakah through payroll deductions within the Directorate General of Treasury Ministry of Finance Republic of Indonesia. The method used in this research is descriptive and multiple regression methods. Descriptive analysis is a systematic overview, factual and accurate as to facts, properties, and the relationship between the phenomena under investigation. While linear regressionis intended to determine whether or not the influence of independent variables on the dependent variable. Samples used in this study as many as 96 respondents. The analysis was using of SPSS version 12. These results indicate that the variables of education, income, religious knowledge and confidence to LAZ significantly affect the employee’s willingness to pay profession zakah through salary reduction. Marital status variable did not significantly affect. Value of coeficient of determination (adjusted R²) is 0876 or 87.6%, which means that the independent variables can explain the dependent variable willingness to pay zakat though employee wage withholding of 87.6%, while the remaining 12.4% is explained by other factors not included in the model.Keywords: willingness to pay, profession zakah, salary reduction.